PENGARUH PARTISIPASI DALAM ORGANISASI MAHASISWA INTERNAL KAMPUS FKIP UNTAN TERHADAP PRESTASI BELAJAR MAHASISWAPENDIDIKAN SOSIOLOGI - Ida Surtiana; Amrazi Zakso; Maria Ulfah (Universitas Tanjungpura, 2022)
The main problem in this study is to find out how the influence of internal student participation of FKIP UNTAN campus on the learning achievement of Sociology Education students. The method used in this study is a descriptive method with a form of quasiative research. The population in the study was 30 students. Furthermore, the data collection technique used is a questionnaire. Then from the data processing techniques used by means of data analysis methods. The results showed 1) student participation in the internal student organization of the campus fkip untan to learning achievement by 37% in the moderate category, 2) the learning achievement of sociology education students who follow the internal campus organization by 83% falls into the high category, 3) tcalculated by 8,866 which is greater than the grade of ttable 1,701 so that Ho was rejected and Ha was accepted which means student participation has an influence on the learning achievement of sociology education students. The coefficient of determination(R2)shows a figure of 0.728 = 72.8%. So, there is an influence of student participation on the learning achievement of sociology education students.